Managing expectations: international criminal trials and the prospects for deterrence of mass atrocity - Cronin-Furman, Kate (International journal of transitional justice, 2013)
Despite high hopes that the proliferation of international justice mechanisms represents progress toward the maintenance of international peace and security, claims about the ability of prosecutions to prevent future atrocities remain largely unexamined. These claims rely on undertheorized assumptions about both the operation of deterrence and the commission of mass atrocity. This article surveys the theory of criminal deterrence in order to assemble a more clearly specified set of expectations about how deterrence might be expected to operate in the international arena. It invokes social science findings that mass atrocity commission is motivated by different logics across cases to suggest that these differences are relevant to the potential extent of a deterrent effect. It considers the current prosecutorial policy of the International Criminal Court and suggests that, given the comparative lack of certainty and severity of sanction represented by the Court’s prosecutions, as well as the selection of perpetrators with powerful incentives to offend, current prosecutorial policy is not well-targeted at producing a deterrent effect.